Management Problems in Implementing Development Works as Perceived by the NGOs: A Case Study in Nagaland, India - Odyuo, M. N.; Patra, N. K.; Makar, A. K. (Indian Journal of Extension Education, 2017)
This study aims to report on management problems in implementing development works as perceived by the NGOs'  employees and measures suggested for improvement in Nagaland, India. In this study 45 NGOs were selected and from  each NGO one higher level of employee was interviewed as respondent. The functional areas of development  management of developmental organizations were taken into consideration in this study viz. Planning, Financing,  Organizing and Leading. The respondents were asked open ended questions to mention most important problems for each  of the functional area of management which they were facing and also to suggest measures for organizational  effectiveness. Important identified problem(s) are donors terms of support and plan not matching properly, untimely and  irregular fund flow, lack of technical staff and frequently relinquishing the organization, lack of proper office space and  furniture, lack of coordination between NGO and Govt. development functionaries, lack of regular supervision of daily  activities in different areas and language problem, and suggestion(s) against the problems are - Flexibility in plan and  scope of modification as per requirement, regular and timely fund flow, consultancy service from resource personnel, GO NGOs collaboration, Popularization of Nagamese Language to address the language and communication problem
Keywords: NGOs; development management; planning; financing; organizing and leading